A Stylistic Analysis of Bisson’s Bears Discover Fire (Journal of the College of Education for Women, 2014)
This paper aims at analyzing Terry Bisson’s short story Bears Discover Fire stylistically by following both Gerard Genette’s theory of narratology (1980) and Short and Leech (1981) strategy for analyzing fictional works. Also trying to examine to what extent these models are applicable in analyzing the selected story. Stylistic analysis procedures help the readers/researchers to identify specific linguistic features in order to support literary interpretation and appreciation of literary texts. Style in fiction concentrates not on what is written, but on how a text is written. Each writer has his own style and techniques which distinguish him from other writers